Análisis y Evaluación Económica Financiera de la Ferretería Comarpi de la Ciudad de Saraguro Periodo 2013 - 2014 - Morocho Cabrera, Sandra Enith (2016)
The main motivation of this thesis is to contribute to the hardware store "COMARPI" since according to the diagnosis of the situation of the company held weaknesses found the same that can be overcome through the implementation of Economic Analysis and Evaluation Financial allowing improve its development in the market; Thus the present work the following objectives developed in compliance. Proposed general objective is to analyze and evaluate Economic and Financially the COMARPI Hardware, City Saraguro period 2013-2014, in order to improve the management and economic and financial performance of the company; Itis given the same performance under the following specific objectives. The first specific objective is: "To apply and interpret financial indicators to determine liquidity, activity, indebtedness and profitability of the company" the same as when applied was determined that the hardware has low liquidity, is highly leveraged by third parties, and profitability is inadequate The second specific objective is to "assess the Financial and Economic Structure, Working Capital, Breakeven, Conversion Cycle Cash, System DUPONT and EVA to measure the efficiency with which have been used 6 economic-financial resources of the company" in which to implement the economic and financial structure was determined that in both periods analyzed inventories represent higher percentage in assets, has very high doubts suppliers, has a positive working capital the same as used for the company to continue operating easily conversion cycle that the company is advantageous because it does not take long to recover the capital invested in applying the EVA was determined that after covering the cost of capital and the owner's expectations a positive value is obtained , also be applied to the balance point it was observed that income in both periods assessed outweigh the costs and expenses of the company. So a report in order to publicize the results of Financial Analysis and Economic Assessment Panel, for proper decision making is also presented. The methodology applied for Financial Analysis and Economic Assessment Panel consisted of a visit to the company to collect relevant and reliable information in order to restructure the financial statements and implement the procedures of analysis and financial evaluation. To proceed to draw the respective conclusions and recommendations. After applying the Analysis and Economic and Financial Evaluation it concluded that the company maintains a high level of merchandise and low inventory turnover, which causes a considerable amount of money is 7 invested and consequently increases the obligations with suppliers. For which the owner is recommended to opt for new credit policies and implement sales strategies (promotions, discounts or other), this would allow greater inventory turnover consequently increased sales.